Pura Vida - Tiszta élet, tiszta gondolat - Kraszkó, Zita (Kultúratudományi Szemle, 2024)
Pura Vida The climate crisis is a present-day concept that is not only hanging over our heads, but if 21st-century man does not change his lifestyle, it could end human existence in the foreseeable future. András Gelencsér's book, Under the spell of illusions, also raises this danger. What is the individual’s responsibility beyond the mundane tasks that barely touch the problem as a whole? How can the man of today change his thinking and his consumer habits, and what motivation can he build in place of consumer hoarding? How does a consumer society cope when it has to learn and incorporate new habits into its life? How can man live his present as a conscious builder, instead of a climate worrier and ecoholic? These are the questions I seek to answer through philosophy.